Education Financing System in Indonesia (Integrated Merangin VHS Institution) - Yahya, Yahya; Hadiyanto, Hadiyanto; Wulandari, Diana (International Journal of Educational Dynamics, 2023)
Education is the initial capital to improve the quality of human resources themselves because with education it is hoped that humans will have high knowledge and skills. However, education cannot be separated from the cost of education itself. The Law (UU) No. 20/2003 concerning "the National Education System" explicitly explained that education financing outside of salaries is 20% of the State Revenue and Expenditure Budget (APBN) and 20% of the Regional Revenue and Expenditure Budget (APBD), while PP No. 19/2005 concerning concerning "the National Education System" explains that education funding includes operational costs which include salaries. The purpose of this research is to find out how the education financing system exists in Indonesia, especially at the Merangin Integrated Vocational High School (VHS), Jambi Province. Therefore education is a shared responsibility both from the government and from the community itself. Quality education requires a high cost. The results of this study indicate that what is the pattern of education financing in Indonesia, especially at the Integrated Merangin VHS institution.